(untitled) (Communications in Computational Physics, 2022)
A coupled gas-kinetic scheme (GKS) and unified gas-kinetic wave-particle (UGKWP) method for the disperse dilute gas-particle multiphase flow is proposed. In the two-phase flow, the gas phase is always in the hydrodynamic regime and is followed by GKS for the Navier-Stokes solution. The particle phase is solved by UGKWP in all regimes from particle trajectory crossing to the hydrodynamic wave interaction with the variation of particle’s Knudsen number. In the intensive particle collision regime, the UGKWP gives a hydrodynamic wave representation for the particle phase and the GKS-UGKWP for the two-phase flow reduces to the two-fluid Eulerian-Eulerian (EE) model. In the rarefied regime, the UGKWP tracks individual particle and the GKS-UGKWP goes back to the Eulerian-Lagrangian (EL) formulation. In the transition regime for the solid particle, the GKS-UGKWP takes an optimal choice for the wave and particle decomposition for the solid particle phase and connects the EE and EL methods seamlessly. The GKS-UGKWP method will be tested in all flow regimes with a large variation of Knudsen number for the solid particle transport and Stokes number for the two-phase interaction. It is confirmed that GKS-UGKWP is an efficient and accurate multiscale method for the gas-particle two-phase flow.